Can occupational health and safety management systems address psychosocial risk factors? An empirical study. (October 2020) - Dahler-Larsen, Peter; Sundby, Anna; Boodhoo, Adiilah
Highlights: OHSMS factors such as management support and employee influence predict action against risks at the workplace. OHSMS factors explain 25.2% of variations in action-taking against psychosocial risks. OHSMS factors explain 20.3% of variations in action-taking against physical risks. Integration of risk assessment into organizational processes is conducive to action taken against psychosocial risks. Abstract: The increasing prevalence of psychosocial risk factors at work poses new challenges to occupational health and safety management systems (OHSMSs) such as those taking place under EU Framework Directive 89/391. Due to the wicked nature of psychosocial risks, management of these risks allegedly lag behind management of other kinds of occupational safety and health risks. Data describing the use of workplace assessments (WPAs) in public workplaces in Denmark (N = 2221) show that variations in OHSMS components predict actions taken against psychosocial risks even better than they predict actions taken against physical risks. Two factors predict actions taken against psychosocial risks in particular: The use of anonymous data in WPAs and the integration of WPAs into organizational processes such as strategy-making and HR. These findings enforce a sustained belief in systematic organizational approaches to the management of psychosocial risk factors.